Dekok and murder on the menu - Baantjer, A.C. (New Amsterdam Publishing, 1992)
On an old menu from the Amsterdam Hotel-Restaurant De Poort van Eden (Eden's Gate) is found the complete, signed confession of a murder.The perpetrator confesses to the killing of a named blackmailer.DeKok and Vledder follow the trail of the menu and soon more victims are found and DeKok and Vledder are in deadly danger themselves.Although the murder was committed in Amsterdam, the case brings them to Rotterdam, Edam and Maastricht, too.